Should Teachers Treat Illiteracy, Hypocalligraphy, and Dysmathematica? - Guerney, Jr., Bernard G. (Canadian Journal of Counselling and Psychotherapy, 2012)
Generally, providers of psychosocial services now have rejected the view that interpersonal and emotional problems are best explained as analogs of disease, but rather have accepted the alternative view that they are learning phenomena. Still to be appreciated, however, is the implication of this change: that it is necessary likewise to reject the clinical treatment component of the medical model in favor of the mass teaching component of the educational model. Until this second step is taken, the providers of psychological services will continue to function deep inside the medical model and outside the educational model. This paper attempts to drive home that point by an allegory showing what might have happened had providers of intellectual services been led astray by the same sort of historical accident that led astray the providers of psychosocial services. Developments which might take place as the educational model takes firmer hold among professionals also are discussed.